Performance Evaluation of Sweet Sorghum Juice and Sugarcane Molasses for Ethanol Production - Hatamipour Mohammad Sadegh (Polish Journal of Chemical Technology, 2015)
Sweet sorghum juice and traditional ethanol substrate i.e. sugarcane molasses were used for ethanol production in this work. At the end of the fermentation process, the sweet sorghum juice yielded more ethanol with higher ethanol concentration compared to sugarcane molasses in all experiments. The sweet sorghum juice had higher cell viability at high ethanol concentrations and minimum sugar concentration at the end of the fermentation process. The ethanol concentration and yield were 8.9% w/v and 0.45 g/g for sweet sorghum in 80 h and 6.5% w/v and 0.37 g/g for sugarcane molasses in 60 h, respectively. The findings on the physical properties of sweet sorghum juice revealed that it has better physical properties compared to sugarcane molasses, resulting to enhanced performance of sweet sorghum juice for ethanol production